Demethylation of leptin promoter in gestational diabetes mellitus: evidence from a mouse model - Hu, Linlin; Liu, Shihuang; Tu, Lin; Zhang, Shupei; Huang, Xiaojing; Lin, Hang; Ji, Jianguang; Yi, Huan; Zheng, Xiangqin (Frontiers in Cell and Developmental Biology, 2026)
BackgroundGestational diabetes mellitus (GDM) has been linked to altered leptin (LEP) gene methylation, which may disrupt maternal glucose metabolism and the associated placental signaling. However, the changes of LEP methylation involved in GDM pathophysiology throughout pregnancy remain unclear.MethodsFemale C57BL/6J mice (6–8 weeks old) were randomly divided into control and GDM groups (n = 40 each). The GDM group was fed a high-fat diet for 4 weeks before mating and given a single streptozotocin injection (120 mg/kg, intraperitoneal injection) on gestational day 2, while controls received standard chow and citrate buffer. Fasting blood glucose and body weight were recorded at baseline, gestational days 5, 12, and 18, and postpartum day 1. Oral glucose tolerance tests (OGTTs) were performed at corresponding stages. Blood was collected for measurement of serum leptin concentrations by ELISA. Leptin protein expression and LEP promoter methylation in decidual tissues were analyzed by Western blot and bisulfite pyrosequencing, respectively. Weighted least-squares regression was used to evaluate the associations between leptin, LEP promoter methylation, and glucose metabolism.ResultsThe high-fat diet and streptozotocin (HFD + STZ) combination successfully induced a GDM phenotype, as evidenced by early and persistent hyperglycemia and impaired glucose tolerance. Serum leptin levels were significantly increased in GDM mice before pregnancy and returned to the levels of pre-pregnancy in postpartum, indicating that the decidua plays an important role in the dynamic regulation of leptin during pregnancy. Western blot analysis confirmed higher leptin expression in the decidual tissue of GDM mice, while bisulfite pyrosequencing revealed significant demethylation of the LEP promoter. WLS analysis showed that leptin upregulation in GDM was closely associated with epigenetic remodeling at specific CpG sites within the LEP promoter, whereas the relationship between promoter demethylation and FBG was altered in GDM.ConclusionDecidual LEP promoter demethylation is associated with hyperleptinemia and shows an epigenetic mechanism linking GDM. LEP promoter demethylation may reflect the metabolic disturbance in GDM and serve as a potential early marker for GDM.